Research on evolution and security risk of Metaverse - Hailong WANG; Yangchun LI; Yuxiao LI (网络与信息安全学报)
Recently, the Metaverse boom has swept the world.To improve the voice in the future digital field, major countries and well-known enterprises have accelerated arrangement of this emerging industry.However, there is no unified definition and ultimate form description of Metaverse.It is urgent to understand the essential characteristics, evolution trend and security risks of Metaverse scientifically, which can promote the high-quality development of China’s electronic information industry and ensure the cyberspace security.With literature research and related information analysis, the definition of Metaverse was put forward based on the core concepts such as technology and application iteration, economic and business model and the role of social relations.Additionally, the development and evolution of Metaverse were divided into four stages (data creation, digital bionics, virtual mirror and virtual-real symbiosis) according to the evolution degree of space category, space-time dimension, key technology and virtual real interaction.And the characteristics and corresponding forms of each stage were expounded.Then it analyzed the main reasons for the popularity of the Metaverse from the perspectives of innovative application demand, virtual life transformation, commercial value driving and political power driving.Focusing on the problems of challenging the national governance system, impacting the mainstream ideology, manipulating the capital market, causing potential social problems and misleading the layout of technology industry, it analyzed the multiple security risks and threats brought by the Metaverse wave from perspectives including politics, culture, economy, society and technology.It is suggested that the Metaverse is still in the stage of concept improvement and product exploration now.China should rationally grasp the development opportunities of the Metaverse based on the current situation of the electronic information industry, prepare for risks in advance, build a digital governance supervision system, stimulate industrial innovation and open development, consolidate the support of network information security, and create a healthy and orderly international environment.